The AI Revolution in Cervical Cancer Screening: Accuracy, Superiority, and the Future of Digital Health - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2024)
Keywords: AI cervical cancer detection, deep learning, cervical cancer screening, colposcopy, digital health, artificial intelligence accuracy
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Machine Learning